Radiographic Diagnosis of Ameloblastoma: A Panoramic Approach - Sami Puspitasari; Lusi Epsilawati; Farina Pramanik (Indonesian Journal of Dentistry, 2026)
Background: Ameloblastoma is a tumor with a relatively high incidence in the jaws. Based on biological behavior, ameloblastomas may be benign or malignant, while radiographic findings further classify them as unicystic or multicystic.Objective: This case report was conducted to identify the similarities and differences between unicystic and multicystic ameloblastoma, focusing on their clinical, radiographic, and histopathological aspects.Case: This report presents two cases involving male patients who were referred to the dental hospital (RSGM) for panoramic radiographic evaluation. Both individuals reported persistent cheek swelling, with Case 1 describing a 19-year-old male who experienced swelling on the right side of the cheek for nearly one year, and Case 2 involving a 43-year-old male with left cheek swelling that had been present for approximately 1.5 years. These cases are included to demonstrate the clinical and radiographic features of the lesions.Discussion: On radiographic evaluation, unicystic and multicystic ameloblastomas shared a radiolucent appearance and jaw involvement; however, they differed in internal structural patterns, locularity, and the definition and cortication of lesion margins.Conclusion: The two cases involved male patients with slowly enlarging, long-standing cheek swelling. Radiographically, both lesions appeared radiolucent, affected the mandibular ramus extending to the temporomandibular joint, and exhibited well-defined, corticated borders with associated cortical destruction, consistent with ameloblastoma. Unicystic ameloblastoma appears as a radiolucent lesion without internal septa and presents with a smoother, well-defined border. In contrast, multicystic ameloblastoma shows internal septa and has a smooth yet less well-defined border